Shifts in the diversity of root endophytic microorganisms across the life cycle of the ratooning rice Jiafuzhan - Dong, Meng; Shi, Longqing; Xie, Zhenxing; Lian, Ling; Zhang, Junian; Jiang, Zhaowei; Wu, Chunzhu (Frontiers in Microbiology, 2023)
The diversity of root endophytic microorganisms, which is closely related to plant life activities, is known to vary with the plant growth stage. This study on the ratooning rice Jiafuzhan explored the diversity of the root endophytic bacteria and fungi, and their dynamics during the plant life cycle. By sequencing the 16S ribosomal ribonucleic acid (16S rRNA) and internal transcribed spacer (ITS) genes, 12,154 operational taxonomic units (OTUs) and 497 amplicon sequence variants (ASVs) were obtained, respectively. The root endophytic microorganisms of rice in the Seedling, Tillering, Jointing, Heading, and Mature stages of the first crop, and at 13, 25, and 60 d after regeneration (at the Heading, Full Heading, and Mature stages of the second crop, respectively) were analyzed using diversity and correlation analyses. There were significant differences in the α- and β-diversity of root endophytic bacteria and fungi by growth stage. Additionally, linear discriminant analysis (LDA) effect size (LEfSe) analysis revealed biomarker bacteria for each growth stage, but biomarker fungi did not exist in every stage. Moreover, the correlation analysis showed that the bacterial and fungal biomarkers interacted with each other. Furthermore, the nitrogen-fixing genus Bradyrhizobium existed in all growth stages. These findings indicate the pattern of root endophytic microorganisms of ratooning rice at different growth stages, and they provide new insights into the high yield of the second crop of ratooning rice (in light of the abundances of various bacteria and fungi).